Fixation mechanisms of nanoparticles on substrates by electron beam irradiation - Morioka, Daichi; Nose, Tomohiro; Chikuta, Taiki; Mitsuishi, Kazutaka; Shimojo, Masayuki (Beilstein Journal of Nanotechnology, 2017)
For applications such as the fabrication of plasmonic waveguides we developed a patterning technique to fabricate an array of nanoparticles on a substrate using focused electron beams (Noriki, T.; Abe, S.;.Kajikawa, K.; Shimojo, M. Beilstein J. Nanotechnol. 2015, 6, 1010–1015). This technique consists of three steps: Firstly, nanoparticles are placed over the entire surface of a substrate. Secondly, the nanoparticles are fixed on the substrate by focused electron beam irradiation. The electron beam decomposes the organic molecules located around the particle into amorphous carbon. The amorphous carbon immobilizes the particle on the substrate. Finally, the unfixed nanoparticles are removed. However, in this original technique, the area in which the nanoparticles were fixed was wider than the electron-probe size of a few nanometers. To understand this widening mechanisms, the effects of accelerating voltage, particle size and substrate material are investigated by means of both experiments and simulation. It is demonstrated that the fixing area is greatly affected by the electrons back-scattered by the substrate. The back-scattering leads to an increase in line width and thus reduces the resolution of this patterning technique.
Keywords: accelerating voltage; electron beam; gold; Monte Carlo simulation; nanoparticle array